On Trusting Neighbors More Than Experts: An Ebola Case Study - Furman, Katherine (Frontiers in Communication, 2020)
In this paper I argue that rumours pose a challenge to effective science communication. I also argue that it is sometimes reasonable for ordinary laypeople to trust rumours over the experts. The argument goes like this. There are strong fact-value entanglements in the sciences. Further, my friends and neighbours may be more likely than the experts to make value judgments that line up with my own. As such, it can make sense for me to pay close attention to their testimony. It may even make sense for me to trust testimony within my peer network – or ‘rumours’ – more than the experts, especially if the experts’ values are especially opaque or suspicious to me. I ground this discussion in the recent West Africa Ebola outbreak, where rumours posed a substantial challenge to containing the epidemic